Analysis of Factors Responsible for Preoperative Anxiety in Patients during the COVID-19 Pandemic at the Surgical Polyclinic of Sanglah General Hospital, Denpasar - I Made Widhi Arthayasa; Ni Luh Putu Thrisna Dewi; Ni Gusti Ayu Putu Triyani; Ketut Lisna Wati (Basic and Applied Nursing Research Journal, 2020)
Surgery often causes anxiety in patients. Preoperative anxiety may cause delays of surgery due to physiological and psychological changes experienced by the patient. Preoperative anxiety is influenced by age, gender, education level, physical condition, and experience. The research objective was to analyze the influence of factors responsible for preoperative anxiety in patients at the Surgical Polyclinic of Sanglah General Hospital, Denpasar, during the COVID-19 pandemic. This research applied cross sectional design with 98 respondents who were selected by consecutive sampling method. Data were collected using the APAIS. Bivariate data analysis was performed using non-parametric Pearson’s chi-squared test and multivariate analysis with logistic regression. All patients experienced preoperative anxiety, most of which were in the moderate category (41.8%). Factors responsible for preoperative anxiety in patients at the Surgical Polyclinic of Sanglah General Hospital, Denpasar, during the COVID-19 pandemic were gender (p = 0.043, α = 0.05), education (p = 0.000, α = 0.05), and experience (p = 0.006, α = 0.05). The most dominant factor was experience with an odds ratio of 4.806. The influence of the three factors was 75.4% and the remaining 24.6% was influenced by other factors. Most respondents expressed their anxiety with fear and curiosity about surgical procedure so it is important for nurses to provide education about the surgery in order to reduce the level of preoperative anxiety in patients, especially female patients with lower levels of educational attainment who have never undergone surgery.